Application of Removable Wrist Splint in the Management of Distal Forearm Torus Fractures - Karimi Mobarakeh, Mahmood (Kowsar Corp., 2013)
BACKGROUND: There is considerable variation in the treatment of distal forearm torus fractures (DFTF), from soft bandaging to cast immobilization. OBJECTIVES: The present study aimed to show the result of removable wrist splint (RWS) in the treatment of these fractures. MATERIALS AND METHODS: One hundred forty two children aged less than 17 years old with DFTF were studied prospectively. These patients were randomly treated either by a short arm cast (SAC) or a RWS for three weeks. Finally the treatment results of the two groups were compared. RESULTS: There were no significant differences regarding degree of pain, compliance or complications between RWS and SAC groups. Resource savings can be made with this approach also patients’ and parents’ satisfaction can be increased without compromising patients' care. CONCLUSIONS: RWS can be considered as an easy and acceptable treatment modality with very low costs and complications in the management of DFTF.